Research on How External Environment Influences Digitalization of Cultural Enterprises - Hao Ji; Yu Pang; Lingling Suo; Tongtong Wang (Discrete Dynamics in Nature and Society)
Digitalization is critical to the growth of cultural industry today. However, existing research has not explained the mechanism by which the external environment affects the digitalization of cultural enterprises. Based on structural equation modeling, we tested the model empirically using data from 295 cultural enterprises in Beijing. The results show that two external environmental variables, the market pressure and the government’s supportive policies, have a positive impact on the adoption of digitalization in cultural enterprises through technical and organizational factors. The research conclusion explains how the external environment influences digitalization in cultural enterprises. Technological factors of digitalization capability and digitalization compatibility and organizational factors of perceived benefits play a mediating role between the external environment and the digitalization of cultural enterprises. Based on these conclusions, we finally put forward a series of countermeasures to enhance the digitalization of cultural enterprises.